Ultra-broadband SnSe-based photothermoelectric detector for mid-infrared gas spectroscopy - Deng, Wenjie (2022)
Seebeck effect is one of the desirable pathways for developing advanced room-temperature (RT) broadband photothermoelectric (PTE) detectors, which are important for infrared spectroscopy applications. However, achieving high performance PTE detectors utilizing materials with high Seebeck coefficient remains a great challenge and further improvements are highly desired. Herein, we introduce a layered material SnSe with high Seebeck coefficient up to 507 ± 20 μV K−1 and further demonstrate an RT ultra-broadband PTE detector ranging from a visible region to a mid-infrared (MIR) region (0.532–13.2 μm). The detector yields a high responsivity of 0.47 V W−1 and a moderate response speed of 107 ms at an excitation wavelength of 8.1 μm at zero bias, which is comparable or higher than those parameters of the commercial products. Moreover, we have retrieved absorption fingerprints of molecular gases during MIR spectroscopy by using this detector owing to its wide response range, which illustrates great potential of this type of broadband high performance PTE detector toward advanced optoelectronics applications.